REGIONAL IMBALANCES IN THE LEVELS OF SOCIO-ECONOMIC DEVELOPMENT IN KOLLEGAL TALUK, CHAMARAJANAGAR DISTRICT - G R, Bhuvanesh; S, Arun Das; M, Ravikumar; Anil, Sawant Shusant (Pena Cendekia Insani, 2025)
Regional disparities are common in almost all nations globally inattentive of whether being under-developed, developing, or developed. With the new conversion of target towards human development, the existence of inequalities on rural development is one of the primary issues faced by developing countries. It attempted to examine the spatial inequalities in the rural amenities in Kollegal taluk, Chamarajanagar district. The level of development is estimated separately for education, health, economic, and communication sectors and the taluk is classified into three categories according to the values of the Aggregate weightage scores. An attempt has been made to analyze the level of regional development among different villages in Kollegal. According to the regional disparity, the development index shows that some regions are far more systematically developed in the center of the taluk headquarters. The result shows that vast disparities in the level of regional overall development lie among various villages of Kollegal. The extent of the infrastructure services sector's development has been shown statistically and favorably related to overall socio-economic development, suggesting that the two sectors' development and expansion have been advancing concurrently throughout the country. The result shows that merely a few villages have the highest scores in overall development.